A Drosophila‐centric view of protein tyrosine phosphatases. Issue 9 (13th March 2015) - Hatzihristidis, Teri; Desai, Nikita; Hutchins, Andrew P.; Meng, Tzu-Ching; Tremblay, Michel L.; Miranda-Saavedra, Diego
Abstract : Most of our knowledge on protein tyrosine phosphatases (PTPs) is derived from human pathologies and mouse knockout models. These models largely correlate well with human disease phenotypes, but can be ambiguous due to compensatory mechanisms introduced by paralogous genes. Here we present the analysis of the PTP complement of the fruit fly and the complementary view that PTP studies in Drosophila will accelerate our understanding of PTPs in physiological and pathological conditions. With only 44 PTP genes, Drosophila represents a streamlined version of the human complement. Our integrated analysis places the Drosophila PTPs into evolutionary and functional contexts, thereby providing a platform for the exploitation of the fly for PTP research and the transfer of knowledge onto other model systems.